Resource estimation through ordinary kriging for area zero ree deposit, Araxá (MG) - de OLIVEIRA, Adriano Santos Delgado [UNESP]; Leite, Washington Barbosa [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
The “Área Zero” deposit is located in the municipality of Araxá, Minas Gerais. It is located in the southern portion of the Brasilia Belt, in the Igneous Province of Alto Paranaíba, inserted in the Barreiro Alkaline-Carbonatitic Complex. The complex is a circular intrusion with approximately 16 km2. It is a dome structure and mineralization is a result of the supergene enrichment of carbonatitic rocks, with high levels of rare earth elements (REE). The study area is located in the northern portion of the complex, in an area of 400x200 m. This study aimed to estimate the resources through ordinary kriging method, using a database from 61 boreholes. Statistical analyses showed a great variability of REE grades. To carry out ordinary kriging, a spherical model was fitted over experimental directional variograms. Plotting experimental variograms in different directions showed that the direction of greater continuity was 22,5/0 and 51 m range. To estimate the REE grade, a block model was built with dimensions of 10x10x3m to estimate resources by units. All the units present in the deposit area are mineralized and the resources of Area Zero deposit totaled 10,5 million tonnes with 4,75% of REE content.
Estimativa de recursos, utilizando o método de krigagem ordinária, para o depósito de terras raras área zero, Araxá (MG)
Keywords: Geology; Ordinary kriging; Rare Earth elements; Resource estimate; Statistic method